2012
DOI: 10.1053/j.ajkd.2012.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Decision to Start Renal Replacement Therapy: Results of a Survey Among European Nephrologists

Abstract: Background:Little is known about the criteria nephrologists use in the decision of when to start renal replacement therapy (RRT) in early referred adult patients. We evaluated opinions of European nephrologists on the decision for when to start RRT.Study Design: European web-based survey. Predictors: Patient presentations described as uncomplicated patients, patients with unfavorable clinical and unfavorable social conditions, or patients with specific clinical, social, and logistical factors.Setting & Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 27 publications
2
54
3
Order By: Relevance
“…This finding contrasts with the findings of a European study that found that women nephrologists aimed to start dialysis at higher eGFRs (12). Although 35% of the nephrologists who responded to the questionnaires in the European study were women, only 15% of the patients in our cohort were cared for by women nephrologists.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This finding contrasts with the findings of a European study that found that women nephrologists aimed to start dialysis at higher eGFRs (12). Although 35% of the nephrologists who responded to the questionnaires in the European study were women, only 15% of the patients in our cohort were cared for by women nephrologists.…”
Section: Discussioncontrasting
confidence: 99%
“…Possibly, HSAs differ in their capacity to accommodate patients with ESRD, competition for patients, incentive to initiate patients at lower eGFRs, and health care intensity (29). In a study of factors that influence the decision to start dialysis among European nephrologists, presence of a waiting list in a dialysis facility was cited as a reason to delay dialysis initiation (12). Also, nephrologists from countries with high incidence of treated ESRD and nephrologists who practiced in forprofit dialysis facilities chose higher eGFR for dialysis initiation and were more likely to initiate their patients early in the presence of advanced age and chronic conditions (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a recent European survey of nephrologists, 11% felt that starting dialysis in patients with eGFR$10.5 ml/min per m 2 was always beneficial, even in the absence of symptoms. 20 The clinical uncertainty about when to start dialysis was reported in Canada, where facility-level variation in eGFR at dialysis initiation was found to be 4.5% after accounting for case mix and facility-level factors. 21 A recent international survey study randomized clinical vignettes presented to nephrologists to contain one of eGFR or serum creatinine and assessed opinions regarding the initiation of dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although symptoms of renal failure may drive dialysis start in the future, a recent European survey of nephrologists found that eGFR is still an important consideration (14). The 2012 Kidney Disease Improving Global Outcomes guidelines on dialysis initiation state that renal failure symptoms are likely to occur at an eGFR of 5-9 ml/min per 1.73 m 2 (15).…”
Section: A Look Aheadmentioning
confidence: 99%